Hindu society -an interpretation - Karve, Irawati (Poona, 1968)
This edition contains two new chapters. The last chapter is more or less the same as chapter 5 in the previous edition. which has been dropped Chapter 6 is wholly new and contains results of the studies of my students bearing on the hypothesis about caste as given in this book.
Keywords: Sociology